Environmental changes in Krossfjorden, Svalbard, since 1950: Benthic foraminiferal and stable isotope evidence. Issue 1 (31st December 2022) - Gamboa-Sojo, Viviana M.; Husum, Katrine; Morigi, Caterina; Divine, Dmitry; Miettinen, Arto
ABSTRACT: Environmental changes for the past ca. 50 years were studied in a short sediment core from inner Krossfjorden, Svalbard, investigating benthic foraminifera and stable isotopes (δ 18 O, δ 13 C). A depth–age model based on anthropogenic 137 Cs time markers indicates that record covers the period from 1955 to 2007 and has sediment accumulation rates of ca. 0.3 to 1 cm/year. The benthic foraminifera are arctic and/or common in glaciomarine environments. Six fauna assemblages were identified using stratigraphically constrained cluster analysis. Benthic foraminiferal fauna assemblages are mainly dominated by Cassidulina reniforme. Elphidium clavatum is dominant from 1973 to 1986 and 2002 to 2007, likely due to greater turbidity in the water column. We interpret the increased percentages of Spiroplectammina biformis over the same intervals to reflect a slightly lower salinity probably caused by meltwater. During a short time period, 1970 to 1973, Stainforthia concava dominates the benthic foraminiferal fauna interpreted to reflect increased productivity within a marginal ice zone. Other species as Islandiella norcrossi, Nonionellina labradorica, Islandiella helenae, and Melonis barleanus also indicate more nutrient-rich waters are present but not very abundant throughout the record probably due to the glacier proximal position of the study site. The stable isotope record (δ 18 O) shows lighter values from 2001 to 2007, which seem to correlate well with oceanographic monitoring data showing increasing core temperatures of West Spitsbergen Current.